The Influence of Product Quality and Design Innovation on Purchasing Decisions in Sewing MSMEs in Marindal Village - Selvi Ndruru; A.M. Hatuaon Sihite (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
This study aims to determine the effect of Product Quality and Design Innovation on consumer Purchasing Decisions. The approach used is a quantitative method with 96 respondents. The results of the analysis show that all statement items are valid and reliable, so they are suitable for use. The data are normally distributed and free from symptoms of multicollinearity and autocorrelation. The t-test results show that Product Quality has a positive and significant effect on Purchasing Decisions with a sig. 0.000, while Design Innovation also has a positive and significant effect with a sig. 0.001. Simultaneously, both variables have a significant effect with an F-count value of 159.072 and a sig. 0.000. The R² value of 0.774 indicates that 77.4% of the variation in purchasing decisions is explained by these two variables. The better the product quality and design innovation, the higher the consumer purchasing decision